1995
DOI: 10.1172/jci118147
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine alters the quantitative and qualitative display of selectins on endothelial cells and neutrophils.

Abstract: Since colchicine-sensitive microtubules regulate the expression and topography of surface glycoproteins on a variety of cells, we sought evidence that colchicine interferes with neutrophil-endothelial interactions by altering the number and/or distribution of selectins on endothelial cells and neutrophils. Extremely low, prophylactic, concentrations of colchicine (IC5. = 3 nM) eliminated the E-selectin-mediated increment in endothelial adhesiveness for neutrophils in response to IL-1 (P < 0.001) or TNFa (P < 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
183
0
8

Year Published

1998
1998
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 338 publications
(193 citation statements)
references
References 38 publications
2
183
0
8
Order By: Relevance
“…It is an alkaloid that exerts its main effect at the cellular level through its interaction with tubulin at the microtubules, inhibiting the motility and exocytosis of cellular granules. Colchicine has a powerful antimitotic effect and may also decrease the expression of adhesion molecules on the surface of neutrophils and endothelial cells (33,34). Therefore, the anti-inflammatory effect of colchicine is probably due to its inhibitory effect on leukocyte chemotaxis (35).…”
Section: Discussionmentioning
confidence: 99%
“…It is an alkaloid that exerts its main effect at the cellular level through its interaction with tubulin at the microtubules, inhibiting the motility and exocytosis of cellular granules. Colchicine has a powerful antimitotic effect and may also decrease the expression of adhesion molecules on the surface of neutrophils and endothelial cells (33,34). Therefore, the anti-inflammatory effect of colchicine is probably due to its inhibitory effect on leukocyte chemotaxis (35).…”
Section: Discussionmentioning
confidence: 99%
“…L-selectin shedding not only occurs in response to cell activation, but also after treatment with nonactivating agents such as mAb against signal-transducing molecules promoting cell aggregation (53, 54) chemical cross-linkers (55), acute phase reactants (56), or drugs with anti-inflammatory properties, including colchicine (57)(58)(59). Although the signaling mechanisms regulating Lselectin shedding are largely undefined, it has been shown that the cleavage of this molecule from the T cell surface can be triggered through multiple independent intracellular signaling pathways that may depend on either PKC or PTK activity (25,45,53,60).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it is attributed due to various proposed actions as disruption of microtubule in neutrophils and inhibiting their migration towards the chemotactic factors, alteration in distribution of adhesion molecules on the surface of both neutrophils and endothelial cells, which significantly inhibit the interaction between WBC and endothelial cells, inhibition of monosodium urate crystal activation of the NLRP3 inflammasome, inhibit the release of IL-1ÎČ and suppression of gene expression. 12,13,14,15 This however is dependent upon the dose of colchicine and duration of treatment; the effect is at both molecular and genetic level. 25 The competitive binding of colchicine to serum albumin was well established 26 and thus supports the selection of appropriate method in study to check the existing variability in targeted pharmaco logical activity.…”
Section: Discussionmentioning
confidence: 99%